AN ANALYSIS OF DIGITAL CONTENT FOR TEACHING NARRATIVE TEXT AS A CURRENT IMPLEMENTATIONS OF ICTS IN EDUCATION AT THE THIRD GRADE OF SMAN 1 SELAYAR - Purnamasari, Ayu; Sangkala, Ismail; Syam, Ummi Khaerati (FKIP Unismuh Makassar, 2022)
The purpose of this thesis was to find out the types of digital content for teaching narrative text at the third grade of SMAN 1 Selayar and to find out how an English teacher used digital content in teaching narrative text. This research used a descriptive qualitative method, the instruments used in this research are observation checklist and structured interview. The observation checklist used to observe an English teacher about the implemented of digital content in teaching process and the structured interview used to know more specific about types of digital content that an English teacher used and how it used in teaching narrative text at the third grade of SMAN 1 Selayar. The results of analysis are: An English teacher in the third grade of SMAN 1 Selayar used power point and video. The teacher used the types so good with some preparations before showing digital content, the process of English teaching used three process; first, introduction of using digital content. Secondly, show the material using digital content and third, giving questions for the students about learning material about narrative text that have shown using digital content.